1997
DOI: 10.1111/j.1399-6576.1997.tb04809.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous dolasetron and ondansetron in prevention of postoperative nausea and vomiting: a multicenter, double‐blind, placebo‐controlled study

Abstract: When given at induction of anesthesia, 50 mg intravenous dolasetron is equivalent to 4 mg ondansetron and superior to 25 mg dolasetron and placebo for the prevention of PONV. All treatments were safely administered and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 23 publications
1
41
0
4
Order By: Relevance
“…An important assumption made in the analysis was that the efficacy of droperidol and dolasetron were similar. This assumption is supported by results of dolasetron PONV prophylaxis trials in which the efficacy rate was 60% which is similar to the results obtained from those studies using ondansetron 6,19,20,21,37,38 Estimation of the efficacy rates for the drugs and placebo in our analysis was complicated by the varying definitions and detection techniques for nausea, vomiting, and overall response to therapy used in the published literature. Sensitivity analysis in our model indicates that the pharmacologic prophylaxis strategies are the least costly when the incidence of PONV in the no prophylaxis group is greater than 52%.…”
Section: Discussionsupporting
confidence: 75%
“…An important assumption made in the analysis was that the efficacy of droperidol and dolasetron were similar. This assumption is supported by results of dolasetron PONV prophylaxis trials in which the efficacy rate was 60% which is similar to the results obtained from those studies using ondansetron 6,19,20,21,37,38 Estimation of the efficacy rates for the drugs and placebo in our analysis was complicated by the varying definitions and detection techniques for nausea, vomiting, and overall response to therapy used in the published literature. Sensitivity analysis in our model indicates that the pharmacologic prophylaxis strategies are the least costly when the incidence of PONV in the no prophylaxis group is greater than 52%.…”
Section: Discussionsupporting
confidence: 75%
“…This assumption is supported by several comparative trials of 5-HT 3 receptor antagonists for the prophylaxis of PONV in which there have been no difference in efficacy. 16,65 Although not all of the 5-HT 3 receptor antagonists have been directly compared, available evidence suggests that there are no clinical advantages of any one agent over the others when used for the prophylaxis of PONV. It should be noted that the majority of 5-HT 3 -treated patients in this analysis received ondansetron (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…11,12,[16][17][18][19][20][21][22][23][24]40,51 As mentioned earlier we have no reason to believe these agents are pharmacologically different which is also supported by several comparative trials of 5-HT 3 receptor antagonists for the prophylaxis of PONV in which there have been no difference in efficacy. 16,65 Although not all of the 5-HT 3 receptor antagonists have been directly compared, available evidence suggests that there are no clinical advantages of any one agent over the others when used for the prophylaxis of PONV. Second, both pediatric and adult patients were included resulting in a heterogeneous patient population limiting the external validity of the overall analysis.…”
Section: Discussionmentioning
confidence: 99%
“…49 Dolasetron 12.5 mg was also found to have similar efficacy to ondansetron 4 mg with a similar side effect profile for the prevention of PONV. 50,51 In an earlier study, dolasetron 50 mg had similar efficacy to ondansetron 4 mg. 52 Similarly, in a multicentre trial, it was demonstrated that 2 mg tropisetron intravenously had similar efficacy and side effect profiles to those of ondansetron 4 mg. 53 This was confirmed in another two trials comparing iv tropisetron 5 mg with ondansetron 4 mg and oral tropisetron 5 mg with ondansetron 16 mg. 54,55 Fujii and colleagues compared the antiemetic efficacy of granisetron 2.5 to 3 mg and ramosetron 0.3 mg in three studies. There was no difference between the two agents in achieving a complete response (no PONV and no antiemetic rescue) during the first 24 hr postoperatively.…”
Section: Receptor Antagonistsmentioning
confidence: 99%